A stress fracture of the lumbar spine in a professional rugby player. Issue 5 (30th November 2006) - Castinel, Bernard H; Adam, Philippe; Prat, Christophe
Abstract : In modern rugby, the spine is subjected to great physical pressure, with an increased number of impacts, on both the cervical and the lumbar spine. This case report illustrates overuse injuries of the lumbar spine in international professional rugby players. A 32-year-old sportsman had been practising rugby for 24 years and was playing for a championship level French team when he started suffering from a right lateral pain in the lumbosacral spine. A CT scan showed a unilateral isthmolysis and a coronal irregular fracture of the right pars interarticularis of L5. This led to discussion of (1) the importance of the decision on the date of return to playing rugby and (2) the future of professional rugby players with chronic spinal injuries.